A Field Experiment Testing Whether Accountability Reduces Racial Gaps in Performance Evaluations - Chang, Edward H.; Kirgios, Erika L.; Arslan, Cansin (Psychological Science, 2026)
Accountability is a commonly recommended intervention to reduce discrimination. However, there have been no field experiments testing whether it reduces discrimination in workplaces. Here we present preregistered analyses of a field experiment conducted at a company ( n = 3,266 managers rating 17,149 employees) testing whether an accountability intervention reduces performance-evaluation gaps between White and racial-minority employees. We did not find evidence that the accountability intervention closes evaluation gaps. These null effects are likely not driven by a lack of statistical power or by inattentive managers, nor is the manipulation ineffective in all contexts—a supplemental online experiment shows that similar treatment language does change decision-making, underscoring a disconnect between findings in hypothetical settings versus real organizations. These results highlight the need for additional field experiments and theorizing to better understand when and why accountability interventions, as they may typically be implemented in organizations, improve diversity-related outcomes.